Application of eculizumab, a terminal complement inhibitor, in the management of atypical hemolytic uremic syndrome in a 14-month-old Chinese pediatric patient: a case report - Wei, Xin; Liu, Xinzhu; Yu, Yingying; Xie, Wei; Luo, Wentao; Tu, Ye; Bu, Shuhong; Guo, Guimei (Frontiers in Pediatrics, 2024)
Eculizumab, a recombined humanized monoclonal antibody which possesses high affinity for the complement protein C5, is a therapeutic agent utilized in the treatment of atypical hemolytic uremic syndrome (aHUS) by inhibiting the terminal complement complex C5b-9.In a pediatric patient with aHUS of 14 months, the administration of eculizumab therapy was accompanied by the inclusion of meningococcal vaccine as part of the national immunization program. Notably, no other antibiotics were administered prior to or during the course of eculizumab treatment. Moreover, there were no occurrences of infusion reactions or meningococcal infections observed throughout the course of treatment. Due to the presence of anti-factor H antibodies and insufficient recovery, glucocorticoids and eculizumab were administered at week 0 and week 1, followed by the initiation of mycophenolate mofetil (MMF) at a dosage of 250 mg (approximately 548 mg/m 2 ) per day starting from Day 10. Due to the recovered of complement antibody after 8 doses of eculizumab, the therapeutic interval was extended from once every 3 weeks to once a month since 9 th administration.We experienced and successfully treated a rare case of aHUS with eculizumab in a 14month-old Chinese pediatric patient.